POLIGAMI DALAM PERSPEKTIF HUKUM ISLAM (Kajian Tafsir Muqaranah) - Ichsan, M (IAIN Batusangkar, 2018)
The controversy of the polygamy issues among scholars occurred very sharply, which is almost difficult to find an agreement. Some contemporary scholars are more likely to disagree with the practice of polygamy. The controversy among the scholars in judging the practice of polygamy in society is the author’s reason to examine more specifically the issue in order to get answers to the disputed problems. This research is a library research. It was done by collecting data from books that are related to the problems. This research is descriptive comparative, which studies the comparison of an object, in this case is polygamy according to the Islamic law perspective in the study of the muqaranah (comparison) interpretation. The results of the study is that the controversy of the views of the scholars in terms of polygamy is due to differences in the way of interpreting lafaz amar (marriage orders), namely in the sentence (فانكحوا). Most scholars think that lafaz amar shows to ibahah. Ahlu al-Zhahiryah mentioned that the command of marriage in the surah al-Nisa verse 3 means (obligation) to carry out the order of marriage. Al-Tabariy interpreted that the command to marry in the sentence (فانكحوا) contained in verse 3 of the surah an-Nisa does not mean an obligatory and binding (الالزام) but a teaching الارشاد and notification الاعلام. This is due to the existence of qarinah which turns away the meaning.